A Novel Simple Phantom for Verifying the Dose of Radiation Therapy. (26th March 2015) - Lee, J. H.; Chang, L. T.; Shiau, A. C.; Chen, C. W.; Liao, Y. J.; Li, W. J.; Lee, M. S.; Hsu, S. M.
Abstract : A standard protocol of dosimetric measurements is used by the organizations responsible for verifying that the doses delivered in radiation-therapy institutions are within authorized limits. This study evaluated a self-designed simple auditing phantom for use in verifying the dose of radiation therapy; the phantom design, dose audit system, and clinical tests are described. Thermoluminescent dosimeters (TLDs) were used as postal dosimeters, and mailable phantoms were produced for use in postal audits. Correction factors are important for converting TLD readout values from phantoms into the absorbed dose in water. The phantom scatter correction factor was used to quantify the difference in the scattered dose between a solid water phantom and homemade phantoms; its value ranged from 1.084 to 1.031. The energy-dependence correction factor was used to compare the TLD readout of the unit dose irradiated by audit beam energies with 60 Co in the solid water phantom; its value was 0.99 to 1.01. The setup-condition factor was used to correct for differences in dose-output calibration conditions. Clinical tests of the device calibrating the dose output revealed that the dose deviation was within 3%. Therefore, our homemade phantoms and dosimetric system can be applied for accurately verifying the doses applied in radiation-therapy institutions.